2017
DOI: 10.1001/jamafacial.2016.1782
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Associated With Rhytidectomy Malpractice Litigation Cases

Abstract: IMPORTANCE This study investigates the financial burden of medical malpractice litigation associated with rhytidectomies, as well as factors that contribute to litigation and poor defendant outcomes, which can help guide physician practices.OBJECTIVE To comprehensively evaluate rhytidectomy malpractice litigation.DATA SOURCES AND STUDY SELECTION Jury verdict and settlement reports related to rhytidectomy malpractice litigations were obtained using the Westlaw Next database. Use of medical malpractice in conjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…Previous studies have shown litigations in plastic surgery are commonly due to a practitioner's lack of expertise, lack of informed consent, and poor cosmetic outcome. 19,20 With the mean monetary award totaling $242,000 and greater than 50% of patients sustaining permanent injury, 14 further regulation of what defines "qualified" is paramount to our healthcare system. Particularly with the exponential increase in facial filler demand and its interdependence with popular media, future news coverage both locally and internationally can play a vital role in public perception and government policies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown litigations in plastic surgery are commonly due to a practitioner's lack of expertise, lack of informed consent, and poor cosmetic outcome. 19,20 With the mean monetary award totaling $242,000 and greater than 50% of patients sustaining permanent injury, 14 further regulation of what defines "qualified" is paramount to our healthcare system. Particularly with the exponential increase in facial filler demand and its interdependence with popular media, future news coverage both locally and internationally can play a vital role in public perception and government policies.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is a paucity of well-designed studies analyzing malpractice litigation specific to rhinoplasty. [6][7][8]15,17 The most complete of these studies, published in the Laryngoscope in 2013, reports an analysis of court records pertaining to several different FPS procedures. 6 In their analysis of rhinoplasty-specific claims, the authors used medical malpractice and rhinoplasty as their sole search terms and identified 24 cases related to rhinoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Westlaw and WestlawNext have been used repeatedly to analyze medical malpractice litigation. 6,15,16,[18][19][20] Nexis Uni (formerly LexisNexis Academic) is a subscription-based database which provides access to more than 17 000 business and legal sources from LexisNexis. Nexis Uni has 3 primary collections, 1 of which contains full-text legal documents, including US Federal and State court cases, and law reviews from the late 18th century to present.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased reliability of Web site information provides benefits to the practicing surgeon beyond the possibility of increased Web site traffic; better-informed patients are more often satisfied with their results and less likely to be involved in malpractice litigation. [26][27][28] Also, Web site relia-bility and patient trust are associated with the qualifications of the Web site author. Hence it is critical to facilitate access to information on the surgeon's training and board certification status.…”
Section: Discussionmentioning
confidence: 99%